Genomics, Exometabolomics, and Metabolic Probing Reveal Conserved Proteolytic Metabolism of Thermoflexus hugenholtzii and Three Candidate Species From China and Japan - Thomas, Scott C.; Payne, Devon; Tamadonfar, Kevin O.; Seymour, Cale O.; Jiao, Jian-Yu; Murugapiran, Senthil K.; Lai, Dengxun; Lau, Rebecca; Bowen, Benjamin P.; Silva, Leslie P.; Louie, Katherine B.; Huntemann, Marcel; et al. (Frontiers in Microbiology, 2021)
Thermoflexus hugenholtzii JAD2T, the only cultured representative of the Chloroflexi class Thermoflexia, is abundant in Great Boiling Spring (GBS), NV, USA, and close relatives inhabit geothermal systems globally. However, no defined medium exists for T. hugenholtzii JAD2T and no single carbon source is known to support its growth, leaving key knowledge gaps in its metabolism and nutritional needs. Here, we report an integrated analysis of the draft genome of T. hugenholtzii JAD2T and eight closely related metagenome-assembled genomes (MAGs) from geothermal sites in China, Japan, and the U.S.A., along with targeted exometabolomics and 13C metabolic probing of T. hugenholtzii. The Thermoflexus genomes each code for complete central carbon metabolic pathways and an unusually high abundance and diversity of peptidases, particularly Metallo- and Serine peptidase families, along with ABC transporters for peptides and some amino acids. The T. hugenholtzii JAD2T exometabolome provided evidence of extracellular proteolytic activity based on the accumulation of free amino acids. However, several neutral and polar amino acids appear not to be utilized, based on their accumulation in the medium and the lack of annotated transporters. Adenine and adenosine were scavenged, and thymine and nicotinic acid were released, suggesting interdependency with other organisms in situ. Metabolic probing of T. hugenholtzii JAD2T using 13C-labeled compounds provided evidence of oxidation of glucose, pyruvate, cysteine, and citrate, and functioning glycolytic, tricarboxylic acid (TCA), and oxidative pentose-phosphate pathways. However, differential use of position-specific 13C-labeled compounds showed that glycolysis and the TCA cycle were uncoupled. Thus, despite the high abundance of Thermoflexus in sediments of some geothermal systems, they appear to be highly focused on chemoorganotrophy, particularly protein degradation, and may interact extensively with other microorganisms in situ.